The traditional Arab Islamic city: the structure of neighborhood quarters - Dabbour, Loai (Journal of Architecture and Urbanism, 2021)
This paper is concerned with the structure of quarters in traditional Arab Islamic cities. Previous studies have stressed the idea of an urban structure that corresponds to social groupings, in that it is seen as a collection of neighborhood quarters. This spatial model has often provided the rationale for the design of new housing layouts. The purpose of this study is to examine this issue and to argue that the structure of these cities presents a global whole. To achieve this purpose a general and a specific question are addressed. The general question is about the physically sub-areas within the city, and the specific question is about the issue of social groupings and the kind of relation that space has to society. The proposition thus invokes the idea of a physical structure which appears to correspond to a social pattern. The city of Damascus is used as a model of analysis in which the urban structure is described and characterised. The argument is advanced that the traditional Arab Islamic city has a sub-area structure which is historically generated, but whose morphological combination is fine-tuned and adjusted so that the whole comes to dominate and unify the parts.